2014
DOI: 10.3892/ijo.2014.2735
|View full text |Cite
|
Sign up to set email alerts
|

Tetrandrine induces G1/S cell cycle arrest through the ROS/Akt pathway in EOMA cells and inhibits angiogenesis in vivo

Abstract: Tetrandrine, a bisbenzylisoquinoline alkaloid, is known to inhibit tumor cell proliferation and induce apoptosis in cancer models in vitro and in vivo. In the present study, tetrandrine significantly inhibited the proliferation of mouse endothelial cells (EOMA cell) and induced G1/S arrest in EOMA cells, in which the expressions of cyclin D and cyclin E and CDKs were downregulated. Tetrandrine treatment also caused intracellular accumulation of reactive oxygen species (ROS). Pretreatment with NAC, which is a R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…However, ROS overproduction can be toxic to cells owing to their peroxidative activity (10). One proposed anticancer strategy is the use of exogenous ROS-stressing agents or inhibition of endogenous antioxidants to elevate intracellular ROS levels to toxic amounts, triggering cell cycle arrest in the target cancer cell (11). Ginsenosides are triterpene saponins and the major pharmacologically active components extracted from the roots and rhizomes of various Panax species.…”
Section: Kip1mentioning
confidence: 99%
See 1 more Smart Citation
“…However, ROS overproduction can be toxic to cells owing to their peroxidative activity (10). One proposed anticancer strategy is the use of exogenous ROS-stressing agents or inhibition of endogenous antioxidants to elevate intracellular ROS levels to toxic amounts, triggering cell cycle arrest in the target cancer cell (11). Ginsenosides are triterpene saponins and the major pharmacologically active components extracted from the roots and rhizomes of various Panax species.…”
Section: Kip1mentioning
confidence: 99%
“…. ROS are involved in multiple types of chemically induced cell cycle arrest; evidence indicates that increased oxidative stress is associated with cell cycle arrest induced by certain anticancer agents (11,30). Among the protopanaxadiols, ginsenoside-Rb 2 has been demonstrated to significantly increase the expression of genes encoding antioxidant enzymes, including superoxide dismutase and catalase in vitro (31).…”
Section: Kip1mentioning
confidence: 99%
“…Recently, in mouse endothelial cells (EOMA cells), tetrandrine exhibited significant proliferation inhibition and G1/S arrest via down-regulated expression of cyclin D, cyclin E and CDKs. Furthermore, intracellular accumulation of reactive oxygen species (ROS) and the decline of phospho-Akt protein levels play an important role in tetrandrine-induced cell cycle arrest [28]. Specifically, tetrandrine inhibits the proliferation of SUM-149 and SUM-159 breast cancer initiation cells (TICs).…”
Section: Inhibiting Cancer Cell Proliferationmentioning
confidence: 99%
“…Other studies revealed that tetrandrine was capable of triggering apoptosis in 5637 and T24 human bladder cancer cells and in 786-O, 769-P and ACHN human RCC cells in vitro , which was accompanied by the activation of a very strong and prominent caspase cascade and the mitochondrial pathway in a concentration-dependent manner [27, 48]. Additionally, tetrandrine effectively induced the apoptosis of glioma cells in concentration- and time-dependent manners [49] and induced the apoptosis of EOMA cells in vitro and in vivo [28]. …”
Section: Inducing Apoptosis Of Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation